Non-invasive prenatal testing (NIPT): is routinization problematic? - Christoph Rehmann-Sutter; Daniëlle R. M. Timmermans; Aviad Raz (BMC Medical Ethics, 2023)
Abstract Background The introduction and wide application of non-invasive prenatal testing (NIPT) has triggered further evolution of routines in the practice of prenatal diagnosis. ‘Routinization’ of prenatal diagnosis however has been associated with hampered informed choice and eugenic attitudes or outcomes. It is viewed, at least in some countries, with great suspicion in both bioethics and public discourse. However, it is a heterogeneous phenomenon that needs to be scrutinized in the wider context of social practices of reproductive genetics. In different countries with their different regulatory frameworks, different patterns of routines emerge that have different ethical implications. This paper discusses an ethics of routines informed by the perspectives of organizational sociology and psychology, where a routine is defined as a repetitive, recognizable pattern of interdependent organizational actions that is carried out by multiple performers. We favour a process approach that debunks the view – which gives way to most of the concerns – that routines are always blindly performed. If this is so, routines are therefore not necessarily incompatible with responsible decision-making. Free and informed decision-making can, as we argue, be a key criterion for the ethical evaluation of testing routines. If free and informed decision-making by each pregnant woman is the objective, routines in prenatal testing may not be ethically problematic, but rather are defensible and helpful. We compare recent experiences of NIPT routines in the context of prenatal screening programmes in Germany, Israel and the Netherlands. Notable variation can be observed between these three countries (i) in the levels of routinization around NIPT, (ii) in the scope of routinization, and (iii) in public attitudes toward routinized prenatal testing. Conclusion An ethics of routines in the field of prenatal diagnostics should incorporate and work with the necessary distinctions between levels and forms of routines, in order to develop sound criteria for their evaluation.